2022
DOI: 10.1002/aelm.202200024
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Lattice Thermal Conductivity Switching by 3D−2D Crystal Structure Transition in Nonequilibrium (Pb1−xSnx)Se

Abstract: Dynamic control of thermal transport in solid materials is highly desired for thermal management technology. However, the development of a material exhibiting large modulation of thermal conductivity (κ) by external stimuli remains a major challenge. Here, the large κ modulation is reported by the reversible 3D to 2D crystal structure transition in a nonequilibrium solid solution of (Pb1−xSnx)Se, where Pb2+ stabilizes a 3D cubic structure while Sn2+ does a 2D layered structure. The phase boundary of these phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 42 publications
0
22
1
Order By: Relevance
“…We confirmed that the samples with x = 0.6−0.8 were decomposed to mixtures of the 2D and the 3D phases when heated to T > 700 K and cooled back to RT, substantiating that the Pb-rich (Sn 1−x Pb x )S bulks had been in the non-equilibrium phases. Figure 4 compares the 2D−3D (3D−2D) structural phase transition temperature (T tran ), which is determined as the peak temperature of the first differential of the 2D phase fraction as a function of T, for the (Sn 0.2 Pb 0.8 )S bulk, where those of previously reported (Sn 0.5 Pb 0.5 )Se bulk are also shown for comparison 9 to discuss the difference of T tran for SnS and SnSe system. The 2D−3D structural phase transition has large hysteresis in temperature (different transition temperatures under heating and cooling, respectively) as often observed in first-order phase transitions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We confirmed that the samples with x = 0.6−0.8 were decomposed to mixtures of the 2D and the 3D phases when heated to T > 700 K and cooled back to RT, substantiating that the Pb-rich (Sn 1−x Pb x )S bulks had been in the non-equilibrium phases. Figure 4 compares the 2D−3D (3D−2D) structural phase transition temperature (T tran ), which is determined as the peak temperature of the first differential of the 2D phase fraction as a function of T, for the (Sn 0.2 Pb 0.8 )S bulk, where those of previously reported (Sn 0.5 Pb 0.5 )Se bulk are also shown for comparison 9 to discuss the difference of T tran for SnS and SnSe system. The 2D−3D structural phase transition has large hysteresis in temperature (different transition temperatures under heating and cooling, respectively) as often observed in first-order phase transitions.…”
Section: Resultsmentioning
confidence: 99%
“…The T hysteresis of the 2D–3D structural phase transition is characterized by the T window width (Δ T tran ) between the closed and open arrows. The T dependences of the first differential of 2D phase fractions (blue symbols) for (Sn 0.5 Pb 0.5 )Se bulk polycrystals are shown for comparison.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…50,52 However, phonon conduction in the two distinct phases is largely limited by the alloy disorder arising from randomly distributed Pb and Sn atoms, resulting in low thermal conductivity (<1.0 W m À1 K À1 at 300 K). 52 By controlling the phase and fraction x in a solid solution, the 3D charge and 2D phonon transports could be realized for decoupling electron and phonon transport, which is pivotal for enhancing the ZT of thermoelectric materials. Therefore, it is essential to understand whether a PbSnSe 2 crystal, which is the PbSnSe 2 alloy with the shortest periodicity, can be a good thermoelectric material, particularly near the phase-transition temperature where is of practical relevance to reaching high ZT.…”
Section: Introductionmentioning
confidence: 99%